2020
DOI: 10.3390/w12051247
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making Tools to Manage the Microbiology of Drinking Water Distribution Systems

Abstract: This paper uses a two-fold multi-criteria decision-making (MCDM) approach applied for the first time to the field of microbial management of drinking water distribution systems (DWDS). Specifically, the decision-making trial and evaluation laboratory (DEMATEL) was applied removing the need for reliance on expert judgement, and analysed interdependencies among water quality parameters and microbiological characteristics of DWDS composed of different pipe materials. In addition, the fuzzy technique for order pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…When looking more closely at the composition of the biofilm bacterial communities, Proteobacteria dominated across all the loops, yet there were differences in the composition of the less abundant community members between the loops. Carpitella et al (2020) showed that it is not always the most abundant microorganisms that play a key role in determining the DWDS processes [57]. Thus, these "rare" community members could be influencers on the presence of specific FLA in a given biofilm, as observed in the Spearman correlations.…”
Section: Discussionmentioning
confidence: 98%
“…When looking more closely at the composition of the biofilm bacterial communities, Proteobacteria dominated across all the loops, yet there were differences in the composition of the less abundant community members between the loops. Carpitella et al (2020) showed that it is not always the most abundant microorganisms that play a key role in determining the DWDS processes [57]. Thus, these "rare" community members could be influencers on the presence of specific FLA in a given biofilm, as observed in the Spearman correlations.…”
Section: Discussionmentioning
confidence: 98%